Contexts and Functions of Proverbs in Selected Plays of Ola Rotimi (2013)
Proverbs describe, classify and judge a given situation with emphasis on moral/ethical recommendations. They also point to the life patterns of the society from which they are derived. Many studies have been undertaken on classification and definition of proverbs from various cultures and disciplines. Much attention has also been drawn to Ola Rotimi‘s proverbs from the point of view of pragmatics and sociolinguistics, but enough scholarly attention has not been given to the contexts in which the proverbs have been used to develop characters. Therefore, this study investigates the contexts in which proverbs have been used and how they have helped to develop dramatic characters in selected plays of Ola Rotimi. Aspects of Troike‘s Ethnography of Communication served as the theoretical framework. Three plays of Ola Rotimi which have abundant proverbs and which exhibit thematic and stylistic similarities were purposively selected. These are The Gods Are Not to Blame, Kurunmi, and Our Husband Has Gone Mad Again. One hundred and fifty-six proverbs were identified and selected from the three texts. The proverbs were subjected to content analysis and percentages. Proverbs in the selected plays of Ola Rotimi are used in psychological and socio-cultural contexts. The psychological contexts are characterised by philosophical, religious and crisis-induced proverbs while the socio-cultural contexts are marked by political, moral/ethical and ideological proverbs. Philosophical proverbs are peculiar to major characters in the three texts while minor characters use more of moral/ethical proverbs. Philosophical and crisis-induced proverbs point out the major characters‘ submission to fate in the face of grave socio-political challenges. Ideological proverbs point to predestination and asymmetrical relations reflected in the Yoruba social structure and gender perspectives. Moral/ethical proverbs describe minor characters‘ submission to the influence and manipulation of major characters over social, physical and psychosomatic conditions. In all the three texts, the major characters employ more proverbs than any of the other characters. Traditional title holders, warlords, and political leaders (major characters) employ more proverbs than women, servants and ordinary citizens (minor characters). Out of the 67 proverbs in The Gods Are not to Blame, 38 (56.7%) are cited by Odewale, the king of Kutuje land. Kurunmi cites 36 (53.7%) out of the 67 proverbs used in Kurunmi, while Lejoka Brown alone cites 10 (45.5%) out of the 22 proverbs used in Our Husband Has Gone Mad Again. The predominant speech acts of proverbs include promising, acknowledging (in socio-cultural contexts); denying, criticising and advising (in psychological contexts), respectively performed by major characters and minor characters. Proverbs, used in psychological and socio-cultural contexts, serve to delineate characters in the selected plays of Ola Rotimi. They, thus, add profound meanings to the texts and define their socio-cultural settings. Future studies could compare the character-development potential of proverbs as demonstrated in this study with that of other major Nigerian playwrights in their major plays.